Flexible epoxy‐dispersed liquid crystal membranes of intrinsic thermal conductivity with high voltage orientation molding. Issue 44 (26th August 2022) - Li, Ying; Gong, Changdan; Hou, Zhenzhong; Zhou, Wenying; Liu, Chao; Peng, Longgui; Wu, Yi; Shi, Qin; Cheng, Qiwei
Abstract: Flexible epoxy‐dispersed liquid crystal membranes (EDLC‐ v membranes) with high thermal conductivity were successfully prepared by using of high voltage orientation molding. Liquid crystal monomer (LCM) was uniformly dispersed into flexible epoxy polymers cured by trimethylolpropane tris(3‐mercaptopropionate) (TTMP) or pentaerythritol tetra(3‐mercaptopropionate) (PETMP). In‐plane thermal conductivity (TC// ) of EDLC‐ v membranes reached to 1.47 W m −1  K −1 with LCM content of 30 wt%, which was 5.65 times higher than that of epoxy polymers without LCM (0.26 W m −1  K −1 ). In addition, the tensile strength and elongation at break of EDLC‐ v membranes were up to 27.9 MPa and 92.8%, respectively. The main reasons for high TC// and flexibility of EDLC‐ v membranes are molecular chains' ordered arrangement, crosslinking in epoxy polymers, hydrogen bond interaction, and high voltage orientation molding. This work provided a new and feasible way to prepare intrinsic high thermal conductive polymer materials, as well as flexible epoxy polymers. Abstract : In this work, flexible epoxy‐dispersed liquid crystal membranes with intrinsic thermal conductivity and high tensile strength as well as elongation at break were successfully prepared, mainly due to the molecular chains' ordered arrangement, crosslinking in epoxy polymers, hydrogen bond interaction, and high voltage orientation molding, which promotes microscopic‐ordered structures as well as continuous phonon transmission paths